ANALISIS DU PONT SYSTEM DENGAN TIME SERIES APPROACH (TSA) DAN CROSS SECTIONAL APPROACH (CSA) DALAM PENILAIAN PERUSAHAAN : PT. INDONESIAN PARADISE PROPERTY TBK., PT. JAKARTA INTERNATIONAL HOTELS & DEVELOPMENT TBK., PT. JAKARTA SETIABUDI INTERNATIONAL TBK., DAN PT. MNC LAND TBK PADA TAHUN 2018-2022 - Ovan Heru Abiatmoko; Nardi Sunardi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to assess the financial performance of PT. Indonesian Paradise Property Tbk., PT. Jakarta International Hotels & Development Tbk., PT. Jakarta Setiabudi International Tbk., and PT. MNC Land Tbk. for the period 2018-2022 using the Du Pont System approach with both Cross Sectional Approach (CSA) and Time Series Analysis (TSA). The findings of this study reveal that PT. Indonesian Paradise Property Tbk. has an average ratio of 39.81%, which is higher than the overall sample company average of 35.27%. In contrast, PT. Jakarta International Hotels & Development Tbk. has an average ratio of 32.73%, which is lower than the overall sample company average of 35.27%. PT. Jakarta Setiabudi International Tbk. exhibits an average ratio of 36.92%, surpassing the overall sample company average of 35.27%. On the other hand, PT. MNC Land Tbk. has an average ratio of 33.51%, which is lower than the overall sample company average of 35.27%. The analysis of Return on Assets (ROA) and Return on Equity (ROE) using Time Series Analysis (TSA) over the research period shows fluctuating and decreasing trends. A similar pattern is observed in the analysis of ROA and ROE using Cross Sectional Approach (CSA), indicating less favorable results as they fall below the average ratio of all companies, which is 35.27%. Overall, these findings suggest that all four sampled companies can be characterized as having a LESS THAN SATISFACTORY performance.